Algorithmic transparency, union information rights and strategic litigation - Riccardo Maraga (Italian Labour Law e-Journal, 2025)
The paper aims to analyse the new spaces that the introduction of AI opens up for worker participation within the enterprise. In particular, the paper focuses on the information and consultation rights of trade union recently introduced by national and European legal systems, with special reference to the principle of algorithmic transparency introduced by Italian law (Art. 1-bis, Legislative Decree No. 152 of May 26, 1997) and the collective information rights provided for by Regulation (EU) 2024/1689, which establishes harmonized rules on artificial intelligence, and by the Directive of the European Parliament and Council on the improvement of working conditions at work through digital platforms. Finally, the paper contains critical reflections on the aforementioned regulatory interventions and outlines possible future developments of worker participation in the company.